(3QSGdI aj GdMdI GdeGfYI ef Gdhbas
(3ChdgG (B:s
(3JYdb GdKGfi HGdChd ajfXQ MjfFP ai LejY GdJYdbGJ acd TF cGf JYdbg HeG bHdg cJYdb GdHOd s
(3BNQgG (B:s
(3Ch de jNJGQ Gdhba YdjgG hEdG CNJjQ aCfJ eNjQ ai CjgeG hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B9s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(190) s
Keywords: (3GdeLGejYs